Protein dilution curves in genotypes of Brachiaria humidicola (Rendle) Schweick - Ju?rez, J.; Bola?os, Eduardo; Vargas, L. M.; Medina, S.; Mart?nez-Hern?ndez, P. A. (Cuban Journal of Agricultural Science, 2011)
Twenty ?two Brachiaria humidicola genotypes were evaluated in a split plot design with three repetitions to know the effect of cut age, dry matter production (DMP), and height on the protein content of the genotypes, as well as on the construction of their protein dilution curves, aiming at determining its pertinence as selection tool. The research was conducted from June to September in 2004. The genotype was the main plot, and the cut age (14, 28. 42, 56, and 70 d), the subplot. The variables under study were: height (cm), DMP (t ha-1), and content of crude protein (% DM). The curves were obtained by modeling the ratio of the protein content with the DMP. A system of equations fitted to a dynamic mechanistic model in each of the genotypes was elaborated, comparing their curves through discriminating analysis. The outcomes showed genotype x cut age interaction in the variables (P < 0.05). At 14 d, the highest protein content (10.75 ?1.14 %), the lowest DMP (2.92?1.03 t ha-1) and the lowest height (12.75 ? 5.45 cm) were obtained. Conversely, at 70 d, lower protein content (6.03 ? 0.82 %), higher DMP (11.80 ? 4.07 t ha-1) and height (58.06 ? 9.50 cm) were recorded. The genotypes CIAT-26407 and CIAT-168687 had lower and higher protein dilution, respectively. The protein content was correlated negatively with the DMP and the height (P < 0.001). The means of the parameters of the curves showed a rate of synthesis of dry matter of 0.0312 t d-1 and of protein of 0.2083 t d-1. The discriminating analysis applied to the curves evidenced significant differences (P < 0.05) between the genotypes. It was concluded that the genotypes of B. humidicola and the age cut are a source of variation in the performance of the protein dilution curves, and that these curves can be used as tool to select the genotypes with lowest protein dilution rate as the plant grows. Key words: dry matter production, height, protein, dynamic model, discriminating analysis, protein dilution curves.